Eco-Friendly Revolution in Fingerprint Detection: Synthesis of Zno Nanoparticles Using Durian (Durio Zibethinus) Peel Extract Pakpak Bharat - Sri Adelila Sari; Rani Febriana; Feri Yuni Asiyah Kabeakan (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Fingerprints are a reliable means of forensic identification because ridge patterns are unique and permanent. Conventional fingerprint powders, however, may contain hazardous ingredients that pose health and environmental risks. This study synthesized zinc oxide (ZnO) nanoparticles via a green route using durian peel (Durio zibethinus) extract and evaluated their potential as an eco-friendly latent fingerprint developer. ZnO nanoparticles were characterized by FTIR to identify functional groups, SEM to examine morphology and particle size, and EDX to verify elemental composition. The biosynthesized ZnO showed semi-spherical to granular particles with sizes of 40–90 nm and no severe agglomeration. FTIR indicated hydroxyl and carbonyl groups from durian peel biomolecules, suggesting their role as reducing and stabilizing agents. EDX confirmed dominant Zn (72.5%) and O (15.2%) signals, supporting high purity ZnO formation. Latent fingerprint development was tested using prints from 40 respondents on porous surfaces (black cardboard and oil paper) and nonporous surfaces (microscope slide, aluminum foil, and compact disc). The ZnO nanopowder produced clear ridge patterns and higher contrast on nonporous substrates, while conventional powders tended to leave residues and may require less safe reagents. These results indicate that durian peel derived ZnO nanoparticles are a promising, economical, and environmentally friendly alternative for latent fingerprint visualization and provide added value for agricultural waste utilization in forensic applications.